[INVITED] Porphyrin-nanoassembled fiber-optic gas sensor fabrication: Optimization of parameters for sensitive ammonia gas detection. (May 2018) - Korposh, Sergiy; Kodaira, Suguru; Selyanchyn, Roman; Ledezma, Francisco H.; James, Stephen W.; Lee, Seung-Woo
Highlights: Highly sensitive evanescent wave fiber-optic ammonia gas sensors were fabricated. The sensitivity to ammonia was linear in the concentration range of 0.5–50 ppm. Sensor's response towards ammonia was also checked under different relative humidity. A limit of detection of 0.5 ppm with 10-cycle PDDA/TSPP film was achieved. Abstract: Highly sensitive fiber-optic ammonia gas sensors were fabricated via layer-by-layer deposition of poly(diallyldimethylammonium chloride) (PDDA) and tetrakis(4-sulfophenyl)porphine (TSPP) onto the surface of the core of a hard-clad multimode fiber that was stripped of its polymer cladding. The effects of film thickness, length of sensing area, and depth of evanescent wave penetration were investigated to clearly understand the sensor performance. The sensitivity of the fiber-optic sensor to ammonia was linear in the concentration range of 0.5–50 ppm and the response and recovery times were less than 3 min, with a limit of detection of 0.5 ppm, when a ten-cycle PDDA/TSPP film was assembled on the surface of the core along a 1 cm-long stripped section of the fiber. The sensor's response towards ammonia was also checked under different relative humidity conditions and a simple statistical data treatment approach, principal component analysis, demonstrated the feasibility of ammonia sensing in environmental relative humidity ranging from dry 7% to highly saturated 80%. Penetration depths of the evanescent wave for the optimal sensor configuration were estimated to be 30 and 33 nm at wavelengths of 420 and 706 nm, which are in a good agreement with the thickness of the 10-cycle deposited film (ca. 30 nm).